Synthesis, Physicochemical Characteristics and Plausible Mechanism of Action of an Immunosuppressive Isoxazolo[5,4-e]-1,2,4-Triazepine Derivative (RM33) - Marcin Mączyński; Andrzej Regiec; Aleksandra Sochacka-Ćwikła; Iwona Kochanowska; Maja Kocięba; Ewa Zaczyńska; Jolanta Artym; Wojciech Kałas; Michał Zimecki (MDPI AG, 2021)
Previous studies demonstrated strong anti-inflammatory properties of isoxazolo[5,4-e]-1,2,4-triazepine (RM33) in vivo. The aim of this investigation was to describe synthesis, determine physicochemical characteristics, evaluate biological activities in murine and human in vitro models, as well as to propose mechanism of action of the compound. The compound was devoid of cell toxicity up to 100 μg/mL against a reference A549 cell line. Likewise, RM33 did not induce apoptosis in these cells. The compound stimulated concanavalin A (ConA)-induced splenocyte proliferation but did not change the secondary humoral immune response in vitro to sheep erythrocytes. Nevertheless, a low suppressive effect was registered on lipopolysaccharide (LPS)-induced splenocyte proliferation and a stronger one on tumor necrosis factor alpha (TNFα) production by rat peritoneal cells. The analysis of signaling pathways elicited by RM33 in nonstimulated resident cells and cell lines revealed changes associated with cell activation. Most importantly, we demonstrated that RM33 enhanced production of cyclooxygenase 2 in LPS-stimulated splenocytes. Based on the previous and herein presented results, we conclude that RM33 is an efficient, nontoxic immune suppressor with prevailing anti-inflammatory action. Additionally, structural studies were carried out with the use of appropriate spectral techniques in order to unequivocally confirm the structure of the RM33 molecule. Unambiguous assignment of NMR chemical shifts of carbon atoms of RM33 was conducted thanks to full detailed analysis of 1H, 13C NMR spectra and their two-dimensional (2D) variants. Comparison between theoretically predicted chemical shifts and experimental ones was also carried out. Additionally, N-deuterated isotopologue of RM33 was synthesized to eliminate potentially disturbing frequencies (such as NH, NH2 deformation vibrations) in the carbonyl region of the IR (infrared) spectrum to confirm the presence of the carbonyl group.